The Effectiveness of The Simakan Application Model (Android-Based Counselor Management System) In Improving Guidance and Counseling Management Planning in Mgbk Vocational Schools in The City of Semarang - Awalya, Awalya; Khiyarusholeh, Ujang; Muslikah, Muslikah; Rokhmatika, Nailu; Adytia Oktava, Muhammad; Khafidhotul Labibah, Azmia; Indah Fajrianti, Dian Safitri (Jurnal Bimbingan Konseling, 2023)
Guidance and counseling service activities in schools can now be assisted by technological advances, one of which is online based. The successful performance of counselors as part of the education system is influenced by many factors such as the ability to master the use of technology and the implementation of management. Objective: The aim of this research is to test whether the SIMAKAN Application Model (Android Based Counselor Management System) is effective in improving MGBK Guidance and Counseling Management Planning throughout the City of Semarang. Methods: this research is quantitative research with a quasi-experiment research design with a true experiment approach with the research population, namely guidance and counseling teachers, members of the Semarang City Vocational School MGBK. This research uses a pretest-posttest control group design. Findings: The research results showed that there was an increase after being given training with a range of 5.32 with a significance value > 0.05. Conclusion: The research results show that the SIMAKAN application training has proven to be effective in increasing the competency of Guidance and Guidance Teachers in Semarang City Vocational Schools.